LESSON STUDY IMPLEMENTASI STRATEGI PEMBELAJARAN “CEGERA” BERBASIS PRODUK MENGGUNAKAN METODE THINK PAIR SHARE - Wijayanti, Okto (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to determine the implementation of the "Cegera" learning strategy based on dance products (song movements) in the 6th semester of FKIP UMP student art courses. The study population was 6 students. The method used in this study was carried out in 3 stages, namely plan, do, and see. Data collection techniques used were interview method, observation method, and documentation method. The data analysis used is descriptive qualitative. The results of this study are (1) The implementation of the "Cegera" learning strategy consists of 3 steps, namely the implementation of storytelling strategies, expression and song movements. (2) make students active, cooperate with each other, and responsibility in the learning process. (3) The process of implementing learning strategies is emphasized with pleasant, fun and relaxed conditions so as to enable students to freely express ideas, concepts, exchange opinions, think together, explore and explore. (3) The dance product produced through the implementation of "Ceg" learning was successfully presented in the final semester practice exam. The Quick Strategy Findings can be recommended for dance-based practice courses.